Green synthesis of fluorescent carbon dots from spices for in vitro imaging and tumour cell growth inhibition - Vasimalai, Nagamalai; Vilas-Boas, Vânia; Gallo, Juan; Cerqueira, María de Fátima; Menéndez-Miranda, Mario; Costa-Fernández, José Manuel; Diéguez, Lorena; Espiña, Begoña; Fernández-Argüelles, María Teresa (Beilstein Journal of Nanotechnology, 2018)
Carbon dots have demonstrated great potential as luminescent nanoparticles in bioapplications. Although such nanoparticles appear to exhibit low toxicity compared to other metal luminescent nanomaterials, today we know that the toxicity of carbon dots (C-dots) strongly depends on the protocol of fabrication. In this work, aqueous fluorescent C-dots have been synthesized from cinnamon, red chilli, turmeric and black pepper, by a one-pot green hydrothermal method. The synthesized C-dots were firstly characterized by means of UV–vis, fluorescence, Fourier transform infrared and Raman spectroscopy, dynamic light scattering and transmission electron microscopy. The optical performance showed an outstanding ability for imaging purposes, with quantum yields up to 43.6%. Thus, the cytotoxicity of the above mentioned spice-derived C-dots was evaluated in vitro in human glioblastoma cells (LN-229 cancer cell line) and in human kidney cells (HK-2 non-cancerous cell line). Bioimaging and viability studies were performed with different C-dot concentrations from 0.1 to 2 mg·mL−1, exhibiting a higher uptake of C-dots in the cancer cultures compared to the non-cancerous cells. Results showed that the spice-derived C-dots inhibited cell viability dose-dependently after a 24 h incubation period, displaying a higher toxicity in LN-229, than in HK-2 cells. As a control, C-dots synthesized from citric acid did not show any significant toxicity in either cancerous or non-cancerous cells, implying that the tumour cell growth inhibition properties observed in the spice-derived C-dots can be attributed to the starting material employed for their fabrication. These results evidence that functional groups in the surface of the C-dots might be responsible for the selective cytotoxicity, as suggested by the presence of piperine in the surface of black pepper C-dots analysed by ESI-QTOF-MS.
Keywords: bioimaging; carbon quantum dots; fluorescence; spices

(untitled) - Coto-Garcia, A. M.; Sotelo-González, E.; Fernández-Argüelles, M. T.; Pereiro, R.; Costa-Fernández, J. M.; Sanz-Medel, A. (Anal. Bioanal. Chem., 2011)

(untitled) - Mohapatra, S.; Rout, S. R.; Das, R. K.; Nayak, S.; Ghosh, S. K. (Langmuir, 2016)

(untitled) - Wang, J.; Zhang, Z.; Zha, S.; Zhu, Y.; Wu, P.; Ehrenberg, B.; Chen, J.-Y. (Biomaterials, 2014)

(untitled) - Chong, Y.; Ma, Y.; Shen, H.; Tu, X.; Zhou, X.; Xu, J.; Dai, J.; Fan, S.; Zhang, Z. (Biomaterials, 2014)

(untitled) - Huang, H.; Li, C.; Zhu, S.; Wang, H.; Chen, C.; Wang, Z.; Bai, T.; Shi, Z.; Feng, S. (Langmuir, 2014)

(untitled) - Baker, S. N.; Baker, G. A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Wang, J.; Zhang, P.; Huang, C.; Liu, G.; Leung, K. C.-F.; Wáng, Y. X. J. (Langmuir, 2015)

(untitled) - Xiao, L.; Wang, Y.; Wong, T.; Sun, H. (Nanoscale, 2017)

(untitled) - Das, A.; Gude, V.; Roy, D.; Chatterjee, T.; De, C. K.; Mandal, P. K. (J. Phys. Chem. C, 2017)

(untitled) - Sciortino, A.; Madonia, A.; Gazzetto, M.; Sciortino, L.; Rohwer, E. J.; Feurer, T.; Gelardi, F. M.; Cannas, M.; Cannizzo, A.; Messina, F. (Nanoscale, 2017)

(untitled) - Righetto, M.; Privitera, A.; Fortunati, I.; Mosconi, D.; Zerbetto, M.; Curri, M. L.; Corricelli, M.; Moretto, A.; Agnoli, S.; Franco, L.; Bozio, R.; Ferrante, C. (J. Phys. Chem. Lett., 2017)

(untitled) - Zhu, S.; Zhang, J.; Tang, S.; Qiao, C.; Wang, L.; Wang, H.; Liu, X.; Li, B.; Li, Y.; Yu, W.; Wang, X.; Sun, H.; et al. (Adv. Funct. Mater., 2012)

(untitled) - Dong, Y.; Wang, R.; Li, G.; Chen, C.; Chi, Y.; Chen, G. (Anal. Chem., 2012)

(untitled) - Chechetka, S. A.; Miyako, E. (ChemistrySelect, 2016)

(untitled) - Bang, J. S.; Oh, D. H.; Choi, H. M.; Sur, B.-J.; Lim, S.-J.; Kim, J. Y.; Yang, H.-I.; Yoo, M. C.; Hahm, D.-H.; Kim, K. S. (Arthritis Res. Ther., 2009)

(untitled) - Velpandian, T.; Jasuja, R.; Bhardwaj, R. K.; Jaiswal, J.; Gupta, S. K. (Eur. J. Drug Metab. Pharmacokinet., 2001)

(untitled) - Bhardwaj, R. K.; Glaeser, H.; Becquemont, L.; Klotz, U.; Gupta, S. K.; Fromm, M. F. (J. Pharmacol. Exp. Ther., 2002)

(untitled) - El-Mofty, M. M.; Khudoley, V. V.; Shwaireb, M. H. (Oncology, 1991)

(untitled) - Aggarwal, B. B.; Kumar, A.; Bharti, A. C. (Anticancer Res., 2003)

(untitled) - Tayyem, R. F.; Heath, D. D.; Al-Delaimy, W. K.; Rock, C. L. (Nutr. Cancer, 2006)

(untitled) - Nagpal, M.; Sood, S. (J. Nat. Sci., Biol. Med., 2013)

Herbal Medicine: Biomolecular and Clinical Aspects - Prasad, S.; Aggarwal, B. B. (Turmeric, the Golden Spice: From Traditional Medicine to Modern Medicine, 2011)

(untitled) - Kang, S. N.; Chung, S. W.; Kim, T. S. (Eur. J. Pharmacol., 2001)

(untitled) - Mori, A.; Lehmann, S.; O'Kelly, J.; Kumagai, T.; Desmond, J. C.; Pervan, M.; McBride, W. H.; Kizaki, M.; Koeffler, H. P. (Cancer Res., 2006)

(untitled) - Aggarwal, B. B.; Kunnumakkara, A. B.; Harikumar, K. B.; Tharakan, S. T.; Sung, B.; Anand, P. (Planta Med., 2008)

(untitled) - Hamidpour, R.; Hamidpour, M.; Hamidpour, S.; Shahlari, M. (J. Tradit. Complementary Med., 2015)

(untitled) - Tabak, M.; Armon, R.; Neeman, I. (J. Ethnopharmacol., 1999)

(untitled) - Farinha, P.; Gascoyne, R. D. (Gastroenterology, 2005)

(untitled) - Quigley, E. M. M. (World J. Gastroenterol., 2006)

(untitled) - Pierrat, P.; Wang, R.; Kereselidze, D.; Lux, M.; Didier, P.; Kichler, A.; Pons, F.; Lebeau, L. (Biomaterials, 2015)

(untitled) - Li, C.-L.; Ou, C.-M.; Huang, C.-C.; Wu, W.-C.; Chen, Y.-P.; Lin, T.-E.; Ho, L.-C..; Wang, C.-W.; Shih, C.-C.; Zhou, H.-C.; Lee, Y.-C.; Tzeng, W.-F.; et al. (J. Mater. Chem. B, 2014)

(untitled) - Hsu, P.-C.; Chen, P.-C.; Ou, C.-M.; Chang, H.-Y.; Chang, H.-T. (J. Mater. Chem. B, 2013)

(untitled) - Sun, X.; Li, Y. (Angew. Chem., Int. Ed., 2004)

(untitled) - Liu, C.; Zhang, P.; Tian, F.; Li, W.; Li, F.; Liu, W. (J. Mater. Chem., 2011)

(untitled) - Li, C.-L.; Huang, C.-C.; Periasamy, A. P.; Roy, P.; Wu, C.-C.; Hsua, C.-L.; Chang, H.-T. (RSC Adv., 2015)

(untitled) - Roy, P.; Chen, P.-C.; Periasamy, A. P.; Chen, Y.-N.; Chang, H.-T. (Mater. Today, 2015)

(untitled) - Qu, D.; Zheng, M.; Du, P.; Zhou, Y.; Zhang, L.; Li, D.; Tan, H.; Zhao, Z.; Xie, Z.; Sun, Z. (Nanoscale, 2013)

(untitled) - Pan, D.; Zhang, J.; Li, Z.; Wu, M. (Adv. Funct. Mater., 2010)

(untitled) - Teng, C.-Y.; Yeh, T.-F.; Lin, K.-I.; Chen, S.-J.; Yoshimura, M.; Teng, H. (J. Mater. Chem. C, 2015)

(untitled) - Li, L.; Wu, G.; Yang, G.; Peng, J.; Zhao, J.; Zhu, J.-J. (Nanoscale, 2013)

(untitled) - Teng, X.; Ma, C.; Ge, C.; Yan, M.; Yang, J.; Zhang, Y.; Morais, P. C.; Bi, H. (J. Mater. Chem. B, 2014)

(untitled) - Zhang, M.; Ju, H.; Zhang, L.; Sun, M.; Zhou, Z.; Dai, Z.; Zhang, L.; Gong, A.; Wu, F.; Du, F. (Int. J. Nanomed., 2015)

(untitled) - Moon, I. K.; Lee, J.; Ruoff, R. S.; Lee, H. (Nat. Commun., 2010)

(untitled) - De Silva, K. S. B.; Gambhir, S.; Wang, X. L.; Xu, X.; Li, W. X.; Officer, D. L.; Wexler, D.; Wallace, G. G.; Dou, S. X. (J. Mater. Chem., 2012)

(untitled) - Sirichote, O.; Hansongnern, K.; Yaochuang, Y.; Jantaraprim, C. (J. Sci. Soc. Thailand, 1996)

(untitled) - Jincheng, W.; Sihao, C. (J. Appl. Polym. Sci., 2010)

(untitled) - Subhan, M. A.; Alam, K.; Rahaman, M. S.; Rahman, M. A.; Awal, R. (J. Sci. Res. (Rajshahi, Bangladesh), 2014)

Natural Products: A Laboratory Guide - Ikan, R. (Academic Press, 1969)

(untitled) - Hosseini, S. I.; Shokri, B.; Firouzjah, M. A.; Kooshki, S.; Sharifian, M. (Thin Solid Films, 2011)

(untitled) - Chu, P. K.; Li, L. (Mater. Chem. Phys., 2006)

(untitled) - Williams, A. T. R.; Winfield, S. A.; Miller, J. N. (Analyst, 1983)

(untitled) - Wang, S.; Chen, Z.-G.; Cole, I.; Li, Q. (Carbon, 2015)